2019
DOI: 10.3389/fmicb.2019.00763
|View full text |Cite
|
Sign up to set email alerts
|

The Macromolecular Basis of Phytoplankton C:N:P Under Nitrogen Starvation

Abstract: Biogeochemical cycles in the ocean are strongly affected by the elemental stoichiometry (C:N:P) of phytoplankton, which largely reflects their macromolecular content. A greater understanding of how this macromolecular content varies among phytoplankton taxa and with resource limitation may strengthen physiological and biogeochemical modeling efforts. We determined the macromolecular basis (protein, carbohydrate, lipid, nucleic acids, pigments) of C:N:P in diatoms and prasinophytes, two globally important phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 102 publications
(142 citation statements)
references
References 126 publications
(201 reference statements)
9
133
0
Order By: Relevance
“…Laboratory studies have shown that almost all the cellular carbon in phytoplankton is accounted for by the major macromolecular pools: proteins (C Pro ), chlorophyll and other pigments (C Chl ), nucleic acids (C Nuc ), carbohydrates (C Carb ), and lipids (C Lip ) (Anderson, 1995;Liefer et al, 2019). The carbon quota of a phytoplankton cell, C Cell (mol C cell −1 ) is thus defined as the sum of these components along with carbon associated with nitrogen storage molecules, C Nsto :…”
Section: Carbon Allocationmentioning
confidence: 99%
See 3 more Smart Citations
“…Laboratory studies have shown that almost all the cellular carbon in phytoplankton is accounted for by the major macromolecular pools: proteins (C Pro ), chlorophyll and other pigments (C Chl ), nucleic acids (C Nuc ), carbohydrates (C Carb ), and lipids (C Lip ) (Anderson, 1995;Liefer et al, 2019). The carbon quota of a phytoplankton cell, C Cell (mol C cell −1 ) is thus defined as the sum of these components along with carbon associated with nitrogen storage molecules, C Nsto :…”
Section: Carbon Allocationmentioning
confidence: 99%
“…Cellular nitrogen (N Cell ) is mostly associated with protein (N Pro ) (Anderson, 1995;Liefer et al, 2019), along with contributions from RNA (N RNA ), DNA (N DNA ), chlorophyll (N Chl ), and nitrogen storage (N Sto ):…”
Section: Nitrogen Allocationmentioning
confidence: 99%
See 2 more Smart Citations
“…With a maximum C:N of 20.2 ± 2.1 for C. decipiens and 29.96 ± 8.4 for E. huxleyi under the iron-replete condition, it can be inferred that a large proportion of the high carbon relative to nitrogen can be attributed to cells suffering from N and/or light limitation. Similarly under Nlimitation, several Thalassiosira species were shown to have C:N ratios over 20 which can be attributed to an accumula-tion of carbohydrates (36). Previous laboratory experiments that mimicked sinking cells with the diatom Pseudo-nitzschia australis grown in excess N relative to Si did not show as dramatic of an increase in C:N suggesting that Si limitation, as can often occur in conjunction with Fe-limited diatoms in the California coastal upwelling region, may influence these elemental stoichiometries (37,38).…”
Section: Resultsmentioning
confidence: 99%